Community assistance on making TESIPDATI tea as an alternative to reduce high blood pressure in Jayapura county - Novianti, Novianti P.E Mambrasar; Debora, Debora P.R Panjaitan; Natalia, Natalia Mendila; Brenda, Brenda S Ayomi; Rohmani, Rohmani; Blestina, Blestina Maryorita (Caring: Jurnal Pengabdian Masyarakat, 2024)
Backgraound : One of the most dangerous non-communicable cardiovascular diseases in the world is hypertension. The World Health Organization states that sustained high blood pressure is characterized by systolic values above 140 mmHg or diastolic values above 90 mmHg. Hypertension, often asymptomatic, can damage vital organs such as the heart, brain, and kidneys, earning it the nickname "silent killer." To reduce and prevent high blood pressure, treatment can be pharmacological, involving the consumption of prescribed medication, or non-pharmacological, such as using traditional remedies like soursop leaf tea. Soursop leaf tea is a herbal drink made from dried soursop leaves formed into tea bags that can be steeped in hot water. It is known that soursop leaves can lower blood pressure, boost the immune system, and possess anti-inflammatory properties due to the acetogenin compounds they contain. Annonacin, muricin, and gigantetrocin are some of the acetogenin compounds found inÂ soursopÂ leaves. The hope is that through training and mentoring in community service activities, especially for alumni and students, sustainability will be achieved, enabling the creation of new job opportunities in the business sector. The objective of Community Service is to socialize and assist the community in making packaged tea using soursop leaves in Sereh Village, Jayapura Regency. Target Audience: The community near the soursop tree plantations, specifically in Sereh Village, Jayapura Regency. Method: Counseling, mentoring on how to make packaged tea from soursop leaves for the mothers in Sereh Village, Jayapura Regency. Target Achievement: Mothers in the community capable of making packaged tea from soursop leaves. The output of the Community Service is the publication of a national community service journal and leaflets on how to make soursop leaf packaged tea to reduce high blood pressure.